CAUSE AND DYNAMICS OF VIOLENCE - Lazić, Siniša D. (Politeia, 2024)
Review of the book "Why Humans Fight: The Social Dynamics of Close-Range Violence" by Siniša Malešević. Through theoretical analysis and empirical research, the author provides a deeper understanding of the factors shaping human behavior in violent situations. Malesevic’s study represents a significant advancement in understanding violence at the micro and meso levels, paving the way for further research and new perspectives in the study of this complex phenomenon.